Ordinance No. 13: An Ordinance in Relation to Offenses Against Public Safety, in CORNING INDEPENDENT, May 16, 1890, at 3, § 3 - (:unkn) unknown (My University, 1890)
§ 3: Any person while exercising the right of carrying arms, and any other person, who shall wrongfully draw or threaten to use any arms to do any other act calculated to cause apprehension or alarm among the citizens of said city, shall, upon conviction thereof before the Police Judge, be fined in any sum not less than one dollar nor more than one hundred dollars.
Keywords: BRANDISHING